Determining the effective strategy-structure fit for multinational corporations (MNCs) : comparison of matrix and hierarchical structure from an informationprocessing perspective - Chiba, Manoj (University of Pretoria, 2017)
Mini Dissertation (MBA)--University of Pretoria, 2017.